2017
DOI: 10.1177/0959354317745589
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of embodiment in cognitive science

Abstract: This article presents an epistemological multilevel analysis of the embodied cognition studies' programme. It is proposed that within the cognitive-embodied type it is possible to find at least four distinct hypotheses regarding the role of the body in human cognition: (a) body-inaction hypothesis, (b) extended body hypothesis, (c) ecological body hypothesis, and (d) body-as-a-physicaldatum hypothesis. The foundations of these hypotheses and some philosophical debates underlying embodiment are discussed in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…When applying embodied cognition theory to teaching and learning solving linear equations, it is assumed that perceptuo-motor knowledge about the action of balancing is a necessary foundation for developing understanding of the mathematical concept of equality (e.g., Antle, Corness, & Bevans, 2013). This perceptuo-motor knowledge is built up from the very pervasive physical experiences we have with balancing from a young age on (Gibbs Jr, 2006), through walking without falling, standing up and sitting down, or holding objects of different weights (Alessandroni, 2018). Furthermore, the other articles in this class of rationales stressed the contribution of concurrent physical experiences with the balance model to the learning of linear equations.…”
Section: Discussion Of the Findings Regarding Why The Model Was Usedmentioning
confidence: 99%
“…When applying embodied cognition theory to teaching and learning solving linear equations, it is assumed that perceptuo-motor knowledge about the action of balancing is a necessary foundation for developing understanding of the mathematical concept of equality (e.g., Antle, Corness, & Bevans, 2013). This perceptuo-motor knowledge is built up from the very pervasive physical experiences we have with balancing from a young age on (Gibbs Jr, 2006), through walking without falling, standing up and sitting down, or holding objects of different weights (Alessandroni, 2018). Furthermore, the other articles in this class of rationales stressed the contribution of concurrent physical experiences with the balance model to the learning of linear equations.…”
Section: Discussion Of the Findings Regarding Why The Model Was Usedmentioning
confidence: 99%
“…First, over the last two decades, a substantial body of research has demonstrated the embodied and situated nature of cognitive processes (Barsalou, 1999(Barsalou, , 2008Marsh, Johnston, Richardson, & Schmidt, 2009;Niedenthal, Barsalou, Winkielman, Krauth-Gruber, & Ric, 2005;Schubert & Semin, 2009; E. R. Smith & Semin, 2004). Perspectives on the specifics of what embodiment entails vary (Alessandroni, 2018;Pouw & Looren de Jong, 2015), but they are consistent in their critiques of the traditional cognitivist framework conceptualizing the mind as an isolated information processor. Instead, one's physical, bodily state is seen as playing a central role in mental activity, implying that psychological activity must be explained not just in terms of representations and mental models but also in terms of the actions of the entire physical organism.…”
mentioning
confidence: 99%
“…Second, there are some who advance philosophical psychologies deeply grounded in the work of one or more classic or recent philosophers and theorists (e.g., Aristotle, Dewey, Husserl, Lacan, Levinas). In a third type of project, the authors advocate for, develop, apply, or seek to improve scientific psychologies that might not (yet) be hegemonic, but that already have some legitimacy within the “mainstream” 5 or can be represented as “roads not taken” (Alessandroni, 2018; Marraffa & Paternoster, 2013; Milkowski et al, 2019; Nielsen & Ward, 2018; Wagoner, 2013).…”
Section: Theory and Psychology For The Time Beingmentioning
confidence: 99%